Association of Scientists for Atomic Education meeting notice - Association of Scientists for Atomic Education (1947)
Meeting notice for the Oak Ridge chapter of the Association of Scientists for Atomic Education (ASAE). The meeting is set to discuss the "1, 2, 3 Creed": No monopoly, no defense, no security without international control.
Keywords: Association of Scientists for Atomic Education; Tennessee--Oak Ridge; Nuclear energy; Cold War (1945-1989)